Changes for Julie - McDonald, Megan (American girls collection., 2007)
Julie is in school detention for passing a note to Joy, a deaf student who has trouble understanding what their teacher is saying. Indignant, Julie decides to run for student body president so she can make changes to the detention system. But the other students are put off by Joy, her choice for vice president, and Julie worries that she'll have little chance of winning if she partners with someone who seems so different. With persistence and creative campaigning, Julie wins the students over--and wins the election without compromising her principles. The "Looking Back" section discusses the 1976 presidential election.--From publisher's description.